IRPLL Formal Movements of Neologism in Pashto Language: Sharif Khan - jan, abdullah (JPL, 2023)
The scholar in this article has shed scholastic light on movements of Neologism formally taken shape in Pashto literature. Though, the roots have been academically drawn-out to the early signs, but specifically engrossed emphasis on formal initiation of Neolgism efforts through systematic approach. In this way, Amir She Ali Khan is dubbed by the linguistics as the first Amir to have launched endeavours on official level to cope with this linguistic phenomena. He established ways and means for this purpose and supervised the efforts to logically deal with this confronting challenge. Apart from Amir’s efforts, the Alamu Academ Kabul, Pashto Academy Peshawar, and the contribution of Abdul Samad Khan Achakzai and Dr. Majawar Ahmed Ziyar have played incomparable role in this direction. The researcher has strived critically to bring forth all those efforts rendered for neologism movements in Pashto literatur